129 Limb girdle muscular dystrophy R12 (LGMD 2L, anoctaminopathy) presenting as refractory myositis: a case series. Issue 6 (27th May 2022) - Marago, Italo; Chinoy, Hector; Roberts, Mark; Roncaroli, Federico; Duplessis, Daniel; Marini-Bettolo, Chiara; Lilleker, James
Abstract : The idiopathic inflammatory myopathy (IIMs) are a rare heterogenous group of immune-mediated diseases leading to muscle inflammation. Prompt and accurate diagnosis is important so that immunosuppressive treatment can commence and irreversible tissue damage be avoided. Other rare conditions may mimic IIM, making confirmation of diagnosis sometimes difficult. Limb girdle muscular dystrophy type R12 (LGMD 2L, anoctaminopathy) is a recessive genetic myopathy which may present in adulthood and is caused by pathogenic variants in the ANO5 gene. Clinical pres- entation can vary from asymptomatic hyper-CK-aemia to exertional myalgia and/or progressive muscle weakness. Here we present four cases of genetically confirmed LGMD R12 who were initially misdiagnosed with IIM. In each case treatment with immunosuppressants, >15 years in one case, was observed without a clear therapeutic response. All patients were negative for anti-nuclear antibodies and all myositis-associated/specific autoantibodies for which testing is available. Prominent fatty infiltration and selective pattern of muscle involvement on muscle magnetic resonance imaging was also observed. The diagnosis of IIM must be carefully considered in autoantibody-negative patients. Adult-onset genetic myopathies, particularly LGMD R12, are differential diagnoses. Avoidance of potentially harmful immu- nosuppressive therapies, genetic counselling, and involvement in research are key benefits of accurate diagnosis in such cases. italo.marago@nhs.net